2011
DOI: 10.1124/mol.111.072314
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Increases Formation of Reactive Oxygen Species and Induces Apoptosis in Postimplantation Embryos: A Role for Oxidative Stress in Valproic Acid-Induced Neural Tube Defects

Abstract: Exposure to the anticonvulsant valproic acid (VPA) during the first trimester of pregnancy is associated with an increased risk of congenital malformations including heart defects, craniofacial abnormalities, skeletal and limb defects, and, most frequently, neural tube defects (NTDs). The mechanisms by which VPA induces teratogenic effects are not fully understood, although previous studies support a role for oxidative stress. To investigate the effects of VPA on early development, a wholeembryo culture model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
98
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(103 citation statements)
references
References 38 publications
4
98
0
Order By: Relevance
“…In previous studies, it was reported that antiepileptic drugs, especially VPA, trigger tissue injury and increase the production of reactive oxygen species by several mechanism and have diverse effects on defence system (20,21). There are many studies that show the elevation of LPO levels in blood and tissues under VPA treatment (20,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was reported that antiepileptic drugs, especially VPA, trigger tissue injury and increase the production of reactive oxygen species by several mechanism and have diverse effects on defence system (20,21). There are many studies that show the elevation of LPO levels in blood and tissues under VPA treatment (20,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…VPA-induced hepatotoxicity and neural tube defects have been reported, and the most likely mechanism is associated with oxidative stress [3,4] .…”
Section: Discussionmentioning
confidence: 99%
“…High-level noise leads to significantly decreased blood flow to the stria vascularis [13] ; then, resolution of the ischemic event by reperfusion leads to an elevation in ROS in the inner ear, which could elevate the levels of antioxidant enzymes (superoxide dismutase, catalase, glutathione peroxidase, glutathione S-transferase, and glutathione reductase) in cochlear tissue [14][15][16][17][18] . Also, oxidative stress has been associated with VPA toxicity [3,4] . Thus, we were interested in the effects of VPA on NIHL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress (OS) is occurred when production process of ROS is accelerated or when the mechanisms involved in keeping cell environment are disordered [1,2]. OS is more likely along with pathological phenomena such as aging, arteriosclerosis, high blood pressure, renal disorders, changes in the immune system, damage to revascularization cycle, nerve damage, cancers and destruction and inflammation conditions [3,4,5,6]. OS can simultaneously result damage in biomolecules including lipids, proteins, nucleic acids and carbohydrates [7,8].…”
Section: Introductionmentioning
confidence: 99%